Using a beginning history teacher’s consideration of students’ prior knowledge in a single lesson case study to reframe discussion of historical knowledge - McCrory, Catherine (Revista Electrónica Interuniversitaria de Formación del Profesorado, 2017)
Using the philosophy of inferentialism (Brandom, 2000), this article explores teachers’ approach to students’ conceptual development, arguing that asking what it is for a concept to have meaning affords new ways of framing both instructional design and explanations of variation in student learning. Through an inductive research strategy into a single lesson taught by a student-teacher, I show how semantic theory can help educators to discern and harness student knowledge building.